(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Chronic renal failure (CKD) is kidney damage defined by a permanent decrease in glomerular filtration rate (GFR) characterized by biological signs present for more than three months. Protein-energy malnutrition (PED) in hemodialysis is also a factor of morbidity and mortality in patients with a prevalence ranging from 15 to 75% worldwide. However, the care of hemodialysis patients often does not include nutritional care. This study aims to contribute to the promotion of the health of patients with chronic renal failure on hemodialysis, by evaluating their nutritional status and identifying the incriminating diets in the deterioration of their health. This is a cross-sectional, prospective and multicenter study, both descriptive and analytical over a period from May 05 to August 05, 2023. It focused on patients with chronic renal failure (CKD) treated with hemodialysis in the clinics Unidial, Martin Luther King and the CMS Maison du Hadj. Nutritional status was assessed using ISRNM 2008 criteria. Mantel Haenszel's Chi-square (? 2 ) test was used to compare proportions, relative risk (RR) to look for associations between variables, and Pearson's coefficient for correlations. It was included 32 patients whose average age was 53.13 14.37 years. The prevalence of protein- energy malnutrition varied from 53.13 to 65.63% depending on the indicator used. A correlation between various malnutrition indicators was found with two risk factors. First, insufficient protein intake: serum albumin was correlated with arm circumference (r = 0.93; p = 0.0001). Second, insufficient energy intake with a BMI strongly correlated with arm circumference (r = 0.96; p = 0.0000). Obesity was present in 6.25% of cases. Abdominal obesity was 43.75% in women and 25% in men. Protein-energy malnutrition is therefore a frequent problem in hemodialysis. It is therefore necessary to improve the hemodialysis program with the integration of adequate and effective nutritional support through lifestyle and dietary interventions in chronic hemodialysis patients.